MicroRNA–mRNA Pairs Associated with Outcome in AML: From In Vitro Cell-Based Studies to AML Patients - Bhise, Neha S.; Chauhan, Lata; Shin, Miyoung; Cao, Xueyuan; Pounds, Stanley; Lamba, Vishal; Lamba, Jatinder K. (Frontiers in Pharmacology, 2016)
Cytarabine is the primary chemotherapeutic agent used for treatment of AML. Disease relapse after initial remission remains one of the most pressing therapeutic challenges in the treatment of AML. Relapsed disease is often resistant to cytarabine and subsequent salvage therapy is ineffective. Recent studies have shown that some miRNAs are associated with prognosis but have not yet explored the role of miRNAs in cellular response to cytarabine. We identified 20 miRNAs that associate with the in vitro cytarabine chemo-sensitivity or apoptotic response of eight AML cell lines. Out of the 20 miRNA, data on 18 miRNAs was available in AML patients from TCGA database. Our stepwise-integrated analyses (step 1- microRNA-target mRNA that were significantly correlated in AML patients; step -2 mRNAs from step 1 with significant association with overall survival (OS) identified 23 unique miRNA-mRNA pairs predictive of OS in AML patients. As expected HOX genes (HOXA9, HOXB7 and HOXA10) were identified to be regulated by miRs as well as predictive of worse OS. Additionally, miR107-Myb, miR-378-granzyme B involved in granzyme signaling and miR10a-MAP4K4 were identified to be predictive of outcome through integrated analysis. Although additional functional validations to establish clinical/pharmacologic importance of microRNA-mRNA pairs are needed, our results from RNA EMSA confirmed binding of miR-10a, miR-378 and miR-107 with their target genes GALNT1, GZMB and MYB respectively. Integration of pathogenic and pharmacologically significant microRNAs and microRNA-mRNA relationships identified in our study opens up opportunities for development of targeted/microRNA-directed therapies.